Metabolic infant nephropathies: a systematic review - A. V. Burlutskaya; N. S. Kovalenko; A. V. Statova (Кубанский научный медицинский вестник, 2021)
Background. Metabolic diseases are growing, also in paediatric practice. Metabolic nephropathy is becoming more prevalent comprising 27–64% total paediatric nephrological cases, according to various published evidence. In this concern, the correct diagnosis, dietary and drug therapy acquire particular importance.Objectives. An overview of current methods for laboratory and instrumental diagnosis and treatment of metabolic nephropathies in children.Methods. National and foreign literature sources were mined in the RSCI, VAK, Scopus, Web of Science, PubMed, Cochrane Library and eLibrary databases at a search depth limited to seven years. The query keywords were: metabolic nephropathy [обменная нефропатия], children [дети], calcium oxalate crystalluria [оксалатно-кальциевая кристаллурия], therapy [терапия]. Content and descriptive analyses were used as research tools.Results. The review surveyed 74 literature sources, with 50 selected for further analysis.Discussion. Modern views on metabolic nephropathies are highlighted in terms of classification, clinical progression, methods of diagnosis, treatment and prevention. A current trend in these diseases is earlier-age morbidity. The most studied metabolic nephropathy is calcium oxalate crystalluria. The article also discusses the role of Oxalobacter formigenes bacteria in secondary oxalate nephropathy.Conclusion. Therapies for metabolic nephropathies as polyaetiologic diseases are multicomponent to target both a causal factor and lithogenesis-contributing mechanisms. Current treatment approaches to metabolic nephropathies in children are highlighted in the light of published knowledge.